3D-printed prostheses in developing countries: A systematic review. Issue 1 (11th February 2022) - Abbady, Hnady E.M.A.; Klinkenberg, Edwin T.M.; de Moel, Lisanne; Nicolai, Noa; van der Stelt, Merel; Verhulst, Arico C.; Maal, Thomas J.J.; Brouwers, Lars
Abstract : Background: According to the World Health Organization, only 5%–15% of people in lower-income countries have access to prostheses. This is largely due to low availability of materials and high costs of prostheses. 3D-printing techniques have become easily accessible and can offer functional patient-specific components at relatively low costs, reducing or bypassing the current manufacturing and postprocessing steps. However, it is not yet clear how 3D-printing can provide a sustainable solution to the low availability of limb prostheses for patients with amputations in lower-income countries. Objective: To evaluate 3D-printing for the production of limb prostheses in lower-income countries and lower–middle-income countries (LLMICs). Study design: Systematic Review. Methods: Literature searches, completed in April 2020, were performed in PubMed, Embase, Web of Science, and Cochrane Library. The search results were independently screened and reviewed by four reviewers. Only studies that examined interventions using prostheses in LLMICs for patients with limb amputations were selected for data extraction and synthesis. The web was also searched using Google for projects that did not publish in a scientific journal. Results: Eighteen studies were included. Results were reported regarding country of use, cost and weight, 3D-printing technology, satisfaction, and failure rate. Conclusion: Low material costs, aesthetic appearance, and the possibility of personalized fitting make 3D-printed prostheses a potential solution for patients with limb amputations in LLMICs. However, the lack of (homogeneous) data shows the need for more published (scientific) research to enable a broader availability of knowledge about 3D-printed prostheses for LLMICs.